Generation and Efficacy of Two Chimeric Viruses Derived from GPE− Vaccine Strain as Classical Swine Fever Vaccine Candidates - Loc Tan Huynh; Norikazu Isoda; Lim Yik Hew; Saho Ogino; Yume Mimura; Maya Kobayashi; Taksoo Kim; Tatsuya Nishi; Katsuhiko Fukai; Takahiro Hiono; Yoshihiro Sakoda (Viruses, 2023)
A previous study proved that vGPE− mainly maintains the properties of classical swine fever (CSF) virus, which is comparable to the GPE− vaccine seed and is a potentially valuable backbone for developing a CSF marker vaccine. Chimeric viruses were constructed based on an infectious cDNA clone derived from the live attenuated GPE− vaccine strain as novel CSF vaccine candidates that potentially meet the concept of differentiating infected from vaccinated animals (DIVA) by substituting the glycoprotein Erns of the GPE− vaccine strain with the corresponding region of non-CSF pestiviruses, either pronghorn antelope pestivirus (PAPeV) or Phocoena pestivirus (PhoPeV). High viral growth and genetic stability after serial passages of the chimeric viruses, namely vGPE−/PAPeV Erns and vGPE−/PhoPeV Erns, were confirmed in vitro. In vivo investigation revealed that two chimeric viruses had comparable immunogenicity and safety profiles to the vGPE− vaccine strain. Vaccination at a dose of 104.0 TCID50 with either vGPE−/PAPeV Erns or vGPE−/PhoPeV Erns conferred complete protection for pigs against the CSF virus challenge in the early stage of immunization. In conclusion, the characteristics of vGPE−/PAPeV Erns and vGPE−/PhoPeV Erns affirmed their properties, as the vGPE− vaccine strain, positioning them as ideal candidates for future development of a CSF marker vaccine.